2008
DOI: 10.1002/pssc.200779291
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Be‐doping on InGaN/GaN nanocolumn light‐emitting diode structures by rf‐plasma‐assisted molecular‐beam epitaxy

Abstract: GaN nanocolumns are one‐dimensional high‐quality dislocation‐free nano‐crystals. The effect of Be‐doping on GaN nanocolumns was investigated using InGaN/GaN nanocolumn LED structure grown by RF‐plasma‐assisted molecular‐beam epitaxy. Be was doped into the upper cladding region of the nanocolumn light‐emitting diodes (LEDs). Be is expected to be a p‐type dopant of GaN with a shallow accepter level, but p‐type conductivity was not obtained in these experiments. However, we observed a remarkable enhancement of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…It has been also said that the variation originates in increases of lateral growth rates in heavily doped nanostructure crystals which are grown on single crystalline substrates. 23,26 Similar effects might occur in the films reported here though the mechanism for the enhancement of the lateral growth rate in this case is still not clear.…”
Section: Resultssupporting
confidence: 65%
“…It has been also said that the variation originates in increases of lateral growth rates in heavily doped nanostructure crystals which are grown on single crystalline substrates. 23,26 Similar effects might occur in the films reported here though the mechanism for the enhancement of the lateral growth rate in this case is still not clear.…”
Section: Resultssupporting
confidence: 65%
“…As reported in Ref. [9], Be doping into the GaN nanocolumns enhanced the lateral growth of nanocolumns to produce a smooth and continuous film on the top surface; the root-mean-square (RMS) surface roughness obtained by atomic force microscope (AFM) observation was markedly reduced from 35 to 10 nm over an area of 20 mm  20 mm upon increasing the Be cell temperature (T Be ) from 710 to 975 1C. From cross-sectional and plan-view transmission electron microscope (TEM) observations of the Be-doped nanocolumn grown at T Be =920 1C, it was observed that the nanocolumn size increased in the Bedoped region due to lateral growth, but the coalescence between nanocolumns was insufficient.…”
Section: Methodsmentioning
confidence: 69%
“…However, the presence of the 5-nm-thick InGaN layer and the short growth time of the GaN nanocolumns do not change the surface morphology. The RMS surface roughnesses with the nanocolumn platforms of T Be =920 and 975 1C were 22.5 and 10.4 nm, respectively [9].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kishino's group first reported the coalescence of top GaN NWs on a silicon substrate. 91,92 They found that Be-or Mg-doping of GaN can remarkably enhance the lateral growth and eventually obtain a smooth and continuous layer with increasing Mg doping concentration. A similar approach was also applied to AlGaN-based UV-A NWs-LED in which the coalesced p-GaN contact layer was successfully demonstrated with the advantage of eliminating the polymer-filling planarization step, thus simplifying fabrication.…”
Section: Coalesced P-contact Layer By Pendeo-epitaxymentioning
confidence: 99%